Intellectual Property Licensing and Transactions Theory and Practice - Contreras, Jorge L. (Social Sciences, 2022)
This textbook covers practical contract drafting and negotiation skills alongside substantive legal doctrine relating to intellectual property transactions and licensing. It is intended primarily for classroom use, but can also serve as a reference work for law students, legal academics, practicing lawyers, and intellectual property professionals.